1999
DOI: 10.1128/jcm.37.4.1150-1153.1999
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 8 Seroprevalence and Evaluation of Nonsexual Transmission Routes by Detection of DNA in Clinical Specimens from Human Immunodeficiency Virus-Seronegative Patients from Central and Southern Italy, with and without Kaposi’s Sarcoma

Abstract: In order to investigate the seroprevalence of human herpesvirus 8 (HHV-8) infection in central and southern Italy, sera from human immunodeficiency virus (HIV)-seronegative subjects, with and without Kaposi’s sarcoma (KS), were analyzed by immunofluorescence assay, using BC-3, a cell line latently infected with HHV-8. High titers of antibody against HHV-8 lytic and latent antigens were detected in all 50 KS patients studied, while in 50 HIV-seronegative subjects without KS, 32 (64%) were found positive for HHV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
11

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 31 publications
3
27
0
11
Order By: Relevance
“…Recent epidemiological studies have suggested that HHV8 could be widespread in the general population, at least in geographic areas where KS is prevalent [3,9–12]. HHV8 seroprevalence rates are reported to be higher in Africa and in Italy than in other geographical regions where KS is less prevalent [13–19]. This observation supports the hypothesis that the prevalence of HHV8 infection is causally related to the incidence of KS.…”
supporting
confidence: 52%
“…Recent epidemiological studies have suggested that HHV8 could be widespread in the general population, at least in geographic areas where KS is prevalent [3,9–12]. HHV8 seroprevalence rates are reported to be higher in Africa and in Italy than in other geographical regions where KS is less prevalent [13–19]. This observation supports the hypothesis that the prevalence of HHV8 infection is causally related to the incidence of KS.…”
supporting
confidence: 52%
“…Epidemiological studies suggested that the prevalence of classic KS could be correlated with the prevalence of HHV-8 infection in a population. 15 In kidney transplant patients, the presence of anti-HHV-8 antibodies was associated with low graft survival and a greater prevalence of KS. 16 HHV-8 also has been consistently found in all forms of KS, effusion lymphoma, and multicentric Castleman's disease.…”
Section: Discussionmentioning
confidence: 99%
“…14±18 Our data suggest that in our population, at low risk for sexually transmitted diseases, other modes of transmission are plausible, as already suggested by previous work. Indeed, HHV8 DNA has been found in tonsils and saliva, 19,32,33 seropositivity has been observed among children and adolescents, 6,34,35 and a relatively linear increase in prevalence of HHV8 infection with age has been demonstrated, as well as an association with hepatitis B infection. 34 There is no doubt that HHV8 infection is associated with KS and a few other diseases, 2 but the differences observed in seroprevalence when considering different general' populations, and not groups at high risk of HIV infection, do not seem to be as strictly related to the incidence of classical KS in different geographical areas 13 as we 19 and others 5,6,24 had previously thought, suggesting that other as yet unknown genetic and/or environmental factors might also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…HHV8 IFA titres were not modified after absorption of the positive sera with the EBV producer P3H-1 cells when TPA induced (American Type Culture Collection). Sensitivity of the test was very high, yielding 100% positive results in patients with classical and iatrogenic KS 19 and approximately 97% positive results in patients with AIDS-related KS.…”
Section: Immunofluorescence Assaymentioning
confidence: 96%